2020
DOI: 10.21203/rs.3.rs-21218/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metformin enhances osteogenic differentiation of stem cells from human exfoliated deciduous teeth through AMPK pathway

Abstract: Stem cells from human exfoliated deciduous teeth (SHEDs) are ideal seed cells in bone tissue engineering. As a first-line anti-diabetic drug, metformin has recently been found to promote bone formation. The purpose of this study was to investigate the effect of metformin on osteogenic differentiation of SHEDs and its underlying mechanism. SHEDs were isolated from the dental pulp of deciduous teeth from healthy children aged from 6 to 12, and their surface antigen markers of stem cells were detected by flow cyt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A potential explanation for this variation may be that metformin was a stimulator for triggering stem cell differentiation into osteogenic lineage. 20,28,33 The number of endogenous stem cells at the wounded ATC interface was approximately equal between the metformin-treated site and the no-metformin control site. The locally applied metformin at the left leg may stimulate more stem cells differentiating into osteogenic lineage.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…A potential explanation for this variation may be that metformin was a stimulator for triggering stem cell differentiation into osteogenic lineage. 20,28,33 The number of endogenous stem cells at the wounded ATC interface was approximately equal between the metformin-treated site and the no-metformin control site. The locally applied metformin at the left leg may stimulate more stem cells differentiating into osteogenic lineage.…”
Section: Discussionmentioning
confidence: 94%
“…Our in vitro research showed that metformin can significantly induce osteogenic differentiation of canine BMSCs, which was consistent with previous studies. 20,28,33 An in vitro study determined that metformin promotes differentiation of human BMSCs into osteoblasts via glycogen synthase kinase-3b inhibition. 20 In another in vitro study, Zhao et al 33 reported that metformin significantly induced osteogenic differentiation of stem cells from human exfoliated deciduous teeth via the adenosine 5#monophosphate-activated protein kinase (AMPK) pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations